The clinical and phenotypical assessment of seronegative villous atrophy; a prospective UK centre experience evaluating 200 adult cases over a 15-year period (2000–2015). Issue 9 (7th September 2016) - Aziz, Imran; Peerally, Mohammad F; Barnes, Jodie-Hannah; Kandasamy, Vigneswaran; Whiteley, Jack C; Partridge, David; Vergani, Patricia; Cross, Simon S; Green, Peter H; Sanders, David S
Abstract : Background: Seronegative villous atrophy (SNVA) is commonly attributed to coeliac disease (CD). However, there are other causes of SNVA. More recently angiotensin-2-receptor-blockers (A2RBs) have been reported as an association but data on SNVA have been limited to centres evaluating complex case referrals and not SNVA in general. Objectives: To provide clinical outcomes and associations in a large prospective study overseeing all newcomers with SNVA. Design: Over a 15-year period (2000–2015) we evaluated 200 adult patients with SNVA at a UK centre. A diagnosis of either seronegative CD (SNCD) or seronegative non-CD (SN-non-CD) was reached. Baseline comparisons were made between the groups, with 343 seropositive CD subjects serving as controls. Results: Of the 200 SNVA cases, SNCD represented 31% (n=62) and SN-non-CD 69% (n=138). The human leucocyte antigen (HLA)-DQ2 and/or DQ8 genotype was present in 61%, with a 51% positive predictive value for SNCD. The breakdown of identifiable causes in the SN-non-CD group comprised infections (27%, n=54), inflammatory/immune-mediated disorders (17.5%, n=35) and drugs (6.5%, n=13; two cases related to A2RBs). However, no cause was found in 18% (n=36) and of these 72% (n=26/36) spontaneously normalised duodenal histology while consuming a gluten-enriched diet. Following multivariable logistic regression analysis an independent factor associated with SN-non-CD was non-white ethnicity (OR 10.8, 95% CI 2.2 to 52.8); in fact, 66% of non-whites had GI infections. On immunohistochemistry all groups stained positive for CD8-T-cytotoxic intraepithelial lymphocytes. However, additional CD4-T helper intraepithelial lymphocytes were occasionally seen in SN-non-CD mimicking the changes associated with refractory CD. Conclusions: Most patients with SNVA do not have CD, in particular those who are not white. Furthermore, a subgroup with no obvious aetiology will show spontaneous histological resolution while consuming gluten. These findings suggest caution in empirically prescribing a gluten-free diet without investigation.